Economic valuation of non-timber forest products from the tropical dry forest: Pijao ethnic, Natagaima, Tolima, Colombia - Pastrana-Aguirre, Gloria Estefanía (2025)
Introduction. Non-timber forest products from tropical dry forests offer multiple benefits and are considered an alternative for the sustainable use of forests and the socioeconomic development of local communities. Nevertheless, little is known about their economic value, limiting the visibility and exploitation of their potential and functionality. Objective. To assess the economic benefits of non-timber forest products from tropical dry forest for the Pijao indigenous population of Natagaima, Tolima, Colombia. Materials and methods. This study was carried out in the municipality of Natagaima, Tolima, Colombia, during the first half of 2023. Data were collected through semi-structured interviews with 95 indigenous people from the rural sector, integrating social, ethnobotanical, and economic variables. For the economic evaluation, the costs required for product acquisition (CRAP), gross profit (BBr), and net profit (Bn) were calculated using direct, indirect, and contingent market valuation methods. Results. A total of 570 reports were registered, identifying 66 tropical dry forest species that offer 122 non-timber forest products, distributed in eight categories of use: food, medicinal, forage, oil, construction, domestic, artisanal, and magical-religious. These products generate a total BBr of 15,000 USD/year, with a CRAP of 6,409 USD and a Bn per person of 8,591 USD/year. The categories of medicinal use, food, and forage bring the greatest economic benefits, contributing 79.5 % (6,830.9 USD/year) of the total net income. Conclusions. Non-timber forest products from tropical dry forests provide important socioeconomic benefits to the livelihoods of the ethnic population studied. The most relevant non-timber forest products are considered to be medicines, food, and forage.